Characteristics and topographical distribution of retinal thinning on optical coherence tomography in Schizophrenics and healthy - Bista, Nabaratna; Shyamsundar, K; Agrawal, Mohini; Rajkarnikar, Sagar; Dhakal, Sachit; Thapa, Kamala; KC, Pradip; Jindal, Imroz (Indonesian Vitreoretinal Society, 2023)
Introduction: To compare results of spectral-domain optical coherence tomography (SD-OCT) like retinal nerve fiber layer (RNFL) and macular thickness (MT) in Schizophrenic patients and healthy individuals. Method: Cross-sectional study. Forty schizophrenic patients and age-gender matched 40 healthy individuals were included in the study. Using SD-OCT, peripapillary RNFL thickness, MT, neuro-retinal rim area (NRR) and mean cup-to-disc ratio (CDR) were measured and compared in 4 quadrants. Results: Mean age of schizophrenic patients was 30.9±7.57years and healthy individuals was 29.65±5.53years (p>0.05). Mean duration of illness was 4.63±2.75 years. Schizophrenic patients showed a significant reduction in overall RNFL thickness (patients: 87.75±8.49µm in the right eye [RE] and 88.42±10.51µm in the left eye [LE]; healthy: 97.75±8.74µm RE and 98±8.744µm LE; p=0.0001 both eyes); except in temporal quadrant. Average MT (patients: 251.92±19.55µm RE and 249.37±22.24µm LE; healthy: 262.07±24.55µm RE and 260.92±23.37µm LE; p=0.044 RE and p=0.026 LE). However, there was no significant difference in central MT (p=0.52 RE, p=0.37 LE), NRR area (p=0.45 RE, p=0.11 LE) and mean CDR (p=0.26 RE, p=0.19 LE) between schizophrenics and healthy. Conclusion: RNFL and macular thickness reduces in schizophrenics when compared to normal, particularly in the superior, inferior and nasal quadrants.